An investigation into drug products withdrawn from the EU market between 2002 and 2011 for safety reasons and the evidence used to support the decision-making. Issue 1 (15th January 2014) - McNaughton, Rhian; Huet, Gwenaël; Shakir, Saad
Abstract : Objectives: The objective of this study was to determine the nature of evidence used to support the withdrawal of marketing authorisations of drug products for safety reasons throughout the European Union (EU) between 2002 and 2011. Setting: Products withdrawn, either by a medicines agency or a marketing authorisation holder, during the period 2002–2011 were identified by conducting detailed searches of the WHO, the European Medicines Agency (EMA) and national medicines agency websites throughout the EU plus Norway, Iceland and Liechtenstein. The scientific evidence used to support the decision was identified from a search within PubMed, the EMA and national medicines agencies websites. Information about spontaneous case reports entered into EudraVigilance and unavailable on the EMA website was received by email from the EMA. Results: 19 drugs were withdrawn from the market, throughout the EU, for safety reasons from 2002 to 2011. Case reports were cited in 95% of withdrawals (18/19) and case–control studies (4/19), cohort studies (4/19), randomised controlled trials (RCTs) (12/19) or meta-analysis (5/19) were cited in 63% of withdrawals (12/19). Cardiovascular events or disorders were the main reason for withdrawal (9/19), followed by hepatic disorders (4/19) and neurological or psychiatric disorders (4/19). Conclusions: This study has shown that the level of evidence used to support drug withdrawal has improved during the past 10 years, with an increased use of case–control studies, cohort studies, RCTs and meta-analyses. This research has demonstrated that such studies have contributed to decision-making in almost two-thirds of cases.